Electrochemical Detection of Ethanol in Air Using Graphene Oxide Nanosheets Combined with Au-WO3 - Aynul Sakinah Ahmad Fauzi; Nur Laila Hamidah; Shota Kitamura; Taiga Kodama; Kosuke Sonda; Ghina Kifayah Putri; Takeshi Shinkai; Muhammad Sohail Ahmad; Yusuke Inomata; Armando T. Quitain; Tetsuya Kida (Sensors, 2022)
Detection, monitoring, and analysis of ethanol are important in various fields such as health care, food industries, and safety control. In this study, we report that a solid electrolyte gas sensor based on a proton-conducting membrane is promising for detecting ethanol in air. We focused on graphene oxide (GO) as a new solid electrolyte because it shows a high proton conductivity at room temperature. GO nanosheets are synthesized by oxidation and exfoliation of expanded graphite via the Tour’s method. GO membranes are fabricated by stacking GO nanosheets by vacuum filtration. To detect ethanol, Au-loaded WO3 is used as the sensing electrode due to the excellent activity of gold nanoparticles for the catalysis of organic molecules. Au-WO3 is coupled with rGO (reduced graphene oxide) to facilitate the electron transport in the electrode. Ce ions are intercalated into the GO membrane to facilitate proton transport. The sensor based on the Ce doped-GO membrane combined with Au-WO3/rGO as a sensing electrode shows good electric potential difference (ΔV) responses to ethanol in the air at room temperature. The sensor signal reaches more than 600 mV in response to ethanol at 40 ppm in air, making it possible to detect ethanol at a few ppb (parts per billion) level. The ethanol sensing mechanism was discussed in terms of the mixed-potential theory and catalysis of ethanol on Au-WO3.